The prevalence of celiac disease among children with short stature - Dawan Dilshad Abdullah; Muhamad Sadraddin Mahmood (Advanced Medical Journal)
Background and objectives: The most important characters of children are growth and development. There are many causes of short stature. Among causes of short stature celiac disease is the important reversible cause. Celiac disease can be diagnosed serologically or/and duodenal biopsy according to the level of serological tests or/and symptoms. The main objective of the study was to find the relation between having high tissue transglutaminase antibody and short stature